Visual Analysis of Protein-Protein Interaction Docking Models Using COZOID Tool - Byska, Jan; Jurcik, Adam; Furmanova, Katarina; Kozlikova, Barbora; Palecek, Jan J (Methods in molecular biology, 2020)
Networks of protein-protein interactions (PPI) constitute either stable or transient complexes in every cell. Most of the cellular complexes keep their function, and therefore stay similar, during evolution. The evolutionary constraints preserve most cellular functions via preservation of protein structures and interactions. The evolutionary conservation information is utilized in template-based approaches, like protein structure modeling or docking. Here we use the combination of the template-free docking method with conservation-based selection of the best docking model using our newly developed COZOID tool.We describe a step-by-step protocol for visual selection of docking models, based on their similarity to the original protein complex structure. Using the COZOID tool, we first analyze contact zones of the original complex structure and select contact amino acids for docking restraints. Then we model and dock the homologous proteins. Finally, we utilize different analytical modes of our COZOID tool to select the docking models most similar to the original complex structure.
Keywords: strukturní homologie proteinů; Protein Binding; Protein Interaction Mapping; proteiny; vazba proteinů; Proteins; Protein Conformation; mapování interakce mezi proteiny; lidé; databáze proteinů; Structural Homology, Protein; konformace proteinů; Databases, Protein; Humans